A New Deep Learning-Based Zero-Inflated Duration Model for Financial Data Irregularly Spaced in Time - Shi, Yong; Dai, Wei; Long, Wen (Frontiers in Physics, 2021)
In stock trading markets, trade durations (i.e. inter-arrival times of trades) usually exhibit high uncertainty and excessive zero values. To forecast conditional distribution of trade duration, this study proposes a hybrid model called DL-ZIACD for short which addresses the problem of excessive zero values by a zero-inflated distribution. Meanwhile, dynamics of the distribution time-varying parameters are captured by a specially designed deep learning (DL) architecture in which the behavioral patterns of large traders and small individual traders are represented separately by different blocks. The proposed hybrid model takes advantage of the strong fitting ability of deep learning methods while allowing for providing a probabilistic output. This paper empirically applied the established model to a large-scale dataset containing 9,900,000 transactions of the Chinese Shenzhen Stock Exchange 100 Index (SZSE 100) constituents. To the best of our knowledge, no previous studies have applied conditional duration models to a dataset of such a large scale. For both the central location forecasting and the extreme quantile forecasting, our proposed model exhibited significant superiority over the benchmark models, which indicates that our DL-ZIACD model can provide accurate forecasts in conditional duration distribution.